Dermatopathology - Kempf, Werner. (Steinkopff : Imprint: Steinkopff, 2008)
A sound background in dermatopathology is essential for the diagnosis of both inflammatory dermatoses and cutaneous tumors. This book provides an introduction to the principles of dermatopathology, aimed primarily at dermatologists and pathologists in training, but useful for a wide audience Everyone interested in dermatopathology will profit from combined knowledge of 4 experienced dermatopathologists uniform structure approach concentrating on common diagnoses logical presentation of clinical and histological features large clearly labeled illustrations clues for differential diagnostic considerations All pictures are in color, printed on high-quality paper, clearly labeled and designed to help every reader become skilled at identifying both patterns and specific diagnostic features rapidly. A dermatopathology designed to be used, not just read—written by practitioners for daily practice.